Which is more effective in introducing Chinese characters? An investigative study of four methods used to teach CFL beginners. Issue 4 (3rd July 2020) - Osborne, Caitríona; Zhang, Qi; Zhang, George Xinsheng
ABSTRACT: This paper presents results of a study investigating four teaching methods used to introduce Chinese characters to beginner learners of Chinese as a foreign language (CFL) in an Irish secondary school between September 2016 and October 2016. Approximately 98 learners aged 14–16 were divided into four groups and taught for two one-hour classes per week. Three groups were taught via rote memorisation (RM), delayed character introduction (DCI) or character colour-coding (CCC), respectively. The fourth (control) group was taught using a unity curriculum approach, focusing on skills of reading, writing, listening and speaking. Two formative evaluations conducted after four weeks and eight weeks assessed development in character recall and recognition, and ability to use characters in written exercises. Preliminary analysis reveals that RM seems to be most effective for short-term memorising of Chinese characters. CCC tends to be useful in acquiring character tone. DCI, although often deemed effective in assisting learners' pronunciation and use of Chinese, did not show significant positive effect in this study. Similarly, the Control group, despite performing slightly better with character use, did not show significant positive effect in this study.